Family conflict and digital risk as determinants of adolescent violence victimization: A cross-sectional study in Depok, Indonesia - Herbawani, Chahya Kharin; Karima, Ulya Qoulan; Agustanti, Rosalia Dika; Ramadhanti, Ismaya; Fitri, Asti Elysia Rahmatul; Riyanti, Febilla Dwinanda (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2026)
Adolescence is increasingly recognized as a period of heightened vulnerability to violence victimization due to rapid bio-psychosocial transitions; however, evidence from Indonesian urban settings remains limited in disentangling family and digital determinants. This study aimed to identify factors associated with adolescent violence in Depok City. A cross-sectional survey was conducted from July to September 2025 among adolescents aged <24 years using self-administered questionnaires distributed via social media with accidental sampling, with 84.2% of respondents female. Associations were examined using Chi-square tests and multivariate logistic regression to control for confounders. The prevalence of adolescent violence was 60.8%, with verbal violence (68.8%) and online violence (47.9%) as the most commonly reported types; perpetrators were most frequently strangers (49.0%) and peers (46.9%). High family conflict was strongly associated with violence victimization (AOR = 8.41; 95% CI: 3.74–18.90; p < 0.001), while high negative social media exposure also increased the odds (AOR = 3.41; 95% CI: 1.53–7.61; p = 0.003), and parenting style functioned as a confounding factor. These findings highlight the need for family-centered prevention emphasizing counseling, positive parenting, and structured parent–adolescent communication, alongside digital literacy to reduce online harm. Integrating islamic values, such as rahmah (compassion), sabr (self-restraint), and islah (reconciliation), may strengthen non-violent communication and emotional support within families and community or faith-based youth programs, thereby contributing to adolescent psychosocial well-being and violence prevention as a public health priority.